2016
DOI: 10.4103/1735-9066.180387
|View full text |Cite
|
Sign up to set email alerts
|

Physical violence against health care workers: A nationwide study from Iran

Abstract: Background:Workplace violence is a serious and problematic phenomenon in health care settings. Research shows that health care workers are at the highest risk of such violence. The aim of this study was to address the frequency of physical violence against Iranian health personnel, their response to such violence, as well as the contributing factors to physical violence.Materials and Methods:A cross-sectional study was conducted in 2011, in which 6500 out of 57,000 health personnel working in some teaching hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
2
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 28 publications
8
62
2
11
Order By: Relevance
“…The findings of quantitative research conducted in Iran suggest that it is possible to compare the frequency of violence in Iran with the frequency of violence observed in international studies (Esmaeilpour, Salsali, & Ahmadi, ; Fallahi‐Khoshknab, Oskouie, Najafi et al., ; Fallahi‐Khoshknab, Oskouie, Najafi et al, ). The Iranian research found that the frequency of violence in psychiatric units was 71% (Fallahi‐Khoshknab, Tamizi, Ghazanfari, & Mehrabani, ) and that the frequencies of sexual and racial harassment were 4.7% and 12%, respectively (Fallahi‐Khoshknab, Oskouie, Ghazanfari et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of quantitative research conducted in Iran suggest that it is possible to compare the frequency of violence in Iran with the frequency of violence observed in international studies (Esmaeilpour, Salsali, & Ahmadi, ; Fallahi‐Khoshknab, Oskouie, Najafi et al., ; Fallahi‐Khoshknab, Oskouie, Najafi et al, ). The Iranian research found that the frequency of violence in psychiatric units was 71% (Fallahi‐Khoshknab, Tamizi, Ghazanfari, & Mehrabani, ) and that the frequencies of sexual and racial harassment were 4.7% and 12%, respectively (Fallahi‐Khoshknab, Oskouie, Ghazanfari et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Workplace violence is the third leading cause of deaths from injuries in the United States and is the second leading cause of women's death in the workplace (2). Healthcare workers are 16 times more likely to experience workplace violence than any other employees (3). Although violence occurs in all workplaces and medical settings, nurses are three times more likely to experience violence than any other healthcare providers due to their close contact with patients and their relatives (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the data testify that nurses and physician assistants are more a subject of violence at work place. There is evidence also in other research that nurses are the main violence victims [15].…”
Section: Resultsmentioning
confidence: 82%
“…At the same time, comparative analysis has proved that the staff who have undergone verbal abuse and have been intimidated/terrorized, received it from the client's next of kin, relatives, workmates and managers; in cases of physical attacks -the clients (89%) and the relatives of a client (22%). The opposite situation was discovered in a research in Iran [15], Pakistan [16,17], and China [18], where the main aggressors have been declared to be the relatives of a client or persons accompanying the client. This situation can be explained if considering social-cultural differences in Iran and Pakistan.…”
Section: Int Conf Society Health Welfare 2016mentioning
confidence: 98%